LEVEL APPLICATION OF GROWERS TO SMART FARMING TECHNIQUES TO CONFRONT CLIMATE CHANGE - Rayan Kadem (Mesopotamia Journal of Agriculture, 2025)
The research aims to measure the level of application of growers to smart farming techniques to confront climate change. The study population included all farmers in Sheikhhan district, totaling 300 farmers. A simple random sample of 40% was selected, resulting in 120 respondents. A questionnaire form consisting of three parts was developed. The first part included the independent variables: age, educational attainment, land area, type of land tenure, and participation in training courses. The second part comprised 50 items to measure the application level, using a three-point scale with three options: (applied extensively, applied moderately, not applied), with weights assigned as (3, 2, 1) accordingly. The third part aimed to identify the problems hindering the application of smart agriculture techniques. Data were collected through personal interviews. Subsequently, the data were coded and prepared for statistical analysis using SPSS software. The results indicated that 69.2% of respondents had a weak application level. Additionally, the results revealed a significant correlation between the independent variables (attitude toward applying smart agriculture, access to information sources, participation in extension activities) and the application level. However, no significant correlation was found between age or educational attainment and the application level. The issue of high costs ranked first with the highest percentage (2.63%). The researcher recommends attracting capital investments into smart agriculture and establishing dedicated communication channels related to food security.